(untitled) (American Journal of Islam and Society, 2005)
Particularly since 9/11, students and the wider public have been asking North American Muslim academics to comment on current events, while Muslim students and the larger Muslim community tend to expect Muslim academics to “defend Islam” by engaging in apologetics. Nonetheless, this book begins by stating that its authors seek to raise the level of discourse about Islam, and want to avoid both apologetics and simplistic answers to complex questions. The introduction makes frank observations about the present state of the world’s Muslims and calls for an intellectual response that seriously engages modern realities. It is followed by fourteen chapters, which are divided into three sections, which deal with contemporary interpretations of Islam, gender issues, and pluralism, respectively. The book concludes with a suggested further reading list and an index ...